Кінетичні закономірності дегідратації бішофіту за терморадіаційного підведення теплоти - Новохат, Олег Анатолійович; Філіпов, Вадим Валерійович; Novokhat, Oleh; Filipov, Vadym (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті досліджено кінетику ізотермічної дегідратації кристалічного бішофіту (MgCl2 · 6H2O) при температурах 70 °C, 90 °C, 100 °C та 110 °C із терморадіаційним нагріванням. На основі експериментальних даних зміни маси бішофіту під час дегідратації отримано графічні залежності зміни ступеня дегідратації та кількості молекул кристалізаційної води в гідраті хлориду магнію. Установлено наявність двох кінетичних стадій процесу, що відображають зміну механізму дегідратації. Розраховано константи швидкості стадій процесу та значення ефективної енергії активації. Отримані результати можуть бути використані для прогнозування швидкості дегідратації бішофіту в технологічних процесах. /// EN: This paper reports an experimental study of the isothermal dehydration kinetics of natural crushed bischofite in its initial hexahydrate form, MgCl2 · 6H2O, under thermoradiative (infrared) heating. The objective was to determine kinetic regularities and to evaluate whether lower hydrates can be obtained in a controlled way in a bulk bed. Experiments were performed on a laboratory thermogravimetric setup with a ceramic IR emitter (≈1 kW). The heat flux was controlled by changing the emitter–bed distance. Steady surface temperatures of 70, 90, 100, and 110 °C were maintained. Continuous mass measurements were used to calculate the dehydration degree, α(τ), and the current number of crystallization-water molecules in the hydrate, n(τ). Raising the temperature accelerated dehydration and increased the final dehydration degree within the same process time from 14 % (70 °C) to 39 % (110 °C). This corresponds to a transition from a hexahydrate–pentahydrate mixture to a tetrahydrate–trihydrate mixture. Linearization of the experimental data with the Avrami–Erofeev equation revealed two kinetic stages. The stages are more pronounced at lower temperatures. Rate constants for stage 1 and stage 2 (k1, k2) were determined for each regime. The ratio k2/k2 was 1.9–2.5 and decreased with temperature. Effective activation energies were estimated from the temperature dependence of the rate constants. The stage behavior is attributed to a change in the controlling factors. Early on, the process is governed mainly by heat input and bond breaking between water and the crystal lattice. Later, internal mass-transfer resistance becomes important due to a partially dehydrated layer that hinders diffusion of water from the crystal interior. The obtained kinetic parameters can support selection of temperature-time modes for partial dehydration (e.g., to tetrahydrate) and prediction of process rates under technological conditions.
Kinetic regularities of bischofite dehydration under thermoradiative heat supply
Keywords: бішофіт; хлорид магнію; гідрат; дегідратація; інфрачервоне випромінювання; bischofite; magnesium chloride; hydrate; dehydration; infrared radiation